The Suitability Analysis of Kampung Pasundan Cisamaya in Mount Ciremai National Park Area as Healing Forest Site - Hikmat Ramdan; Sheilla Ayu Prameswari; Angga Dwiartama (School of Life Sciences and Technology, Institut Teknologi Bandung, 2021)
Forests are ecosystems that are comfortable for human health. Spots from the forest ecosystem site suitable for healing forest must be identified. The research aims to analyze the suitability of Kampung Pasundan Cisamaya (KPC) for healing forest activities. The research method refers to the Draft Indonesian National Standard Number 9006:2021 concerning Forest tourism for health therapy (healing forest). The results showed that the KPC site is suitable for healing forest activities. Five reconnection activities with nature, namely invitation by air, invitation by vegetation, invitation by land, invitation by water, and release emotion, can be carried out well in several spots on KPC's healing forest track. Healing forest activities regularly and adequately has a positive impact on health.